Magnesium alloy surface multilayer anticorrosive coating and preparation method thereof
By depositing the Zr layer on the surface of the magnesium alloy and alternately depositing the ZrN layer and Ta layer, the Ta/ZrN multi-layer structural layer is formed, and the problem of insufficient corrosion resistance and friction resistance caused by defects in the deposition process of magnetron sputtering thin film is solved, and higher corrosion resistance and wear resistance are achieved.
Patent Information
- Application Number
- CN202510085846.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The defects formed during the deposition of existing magnetron sputtering films will reduce the corrosion resistance and friction resistance of the film.
A Zr layer is deposited on the substrate surface and an alternately deposited ZrN layer and Ta layer on the surface of the Zr layer to form a Ta/ZrN multi-layer structural layer, and the anticorrosion coating performance of the magnesium alloy surface is improved through magnetron sputtering process.
It effectively improves the corrosion resistance and wear resistance of the magnesium alloy surface, reduces the internal stress and brittleness of the coating, enhances the bonding strength between the coating and the substrate, avoids the growth of columnar crystals, and improves the density of the coating.
Smart Images

Figure CN119899998A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a multi-layer anti-corrosion coating on the surface of a magnesium alloy and a preparation method thereof. Background Art
[0002] Modern manufacturing places great emphasis on clean energy, recyclable resources, lightweight and structural integration. In this context, magnesium and its alloys have aroused great interest. Compared with other commonly used metal materials, magnesium alloys are lightweight. The density of magnesium is only 1.74g / cm 3 , about 2 / 3 of aluminum and 1 / 4 of steel. Its high machinability and damping capacity give magnesium alloys excellent working performance and are ideal for lightweight manufacturing. However, relative to the standard hydrogen electrode, the standard electrode potential of magnesium is -2.37V, which is lower than aluminum -1.663V and iron -0.440V. It is the most chemically active metal among all structural materials currently available and is prone to corrosion in environments such as humid air and oceans. In addition, magnesium alloys are soft in texture, with a hardness of about 65HV and poor wear resistance. When used in a frictional environment, magnesium alloys often suffer from severe abrasive wear, which ultimately leads to material damage or even failure. In short, the corrosion and wear problems of magnesium alloys have become the main factors restricting their promotion and application.
[0003] In recent years, surface treatment technology has developed rapidly, providing more options for the protection of magnesium alloys. The surface modification methods of magnesium alloys mainly include anodizing, micro-arc oxidation, chemical conversion film, electroplating, chemical plating, sol-gel method, physical vapor deposition, etc. Compared with traditional chemical methods such as electroplating, physical vapor deposition is carried out in a vacuum environment, and the magnesium alloy will not undergo oxidation reaction during the deposition process. And this technology does not contact aqueous solutions or other chemical solutions, and will not corrode the surface of magnesium alloys. Among them, among the PVD technologies with a high degree of industrialization, magnetron sputtering has the characteristics of fast film formation speed, dense and uniform coating, high precision and good adhesion, and has been widely used in many industrial fields.
[0004] Due to the high chemical activity of magnesium, it is extremely sensitive to defects in its surface protective layer. Once the corrosive medium contacts the magnesium substrate, severe corrosion will occur, causing the coating to fall off and fail. Although the coating prepared by magnetron sputtering is of high quality, there may still be a small number of defects that penetrate the entire coating thickness. In addition, when a single-layer coating is prepared by magnetron sputtering, a columnar crystal structure is often formed, and the coarse columnar crystal boundaries can also become channels for corrosive media. Therefore, only by eliminating penetrating defects can the protective coating be fully utilized. Summary of the invention
[0005] In order to solve the problem that defects formed in the existing magnetron sputtering film deposition process will reduce the corrosion resistance and friction resistance of the film, the purpose of the present invention is to provide a multi-layer anti-corrosion coating on the surface of a magnesium alloy and a preparation method thereof.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] A first aspect of the present invention provides a multilayer anti-corrosion coating on the surface of a magnesium alloy, wherein the multilayer anti-corrosion coating comprises a Zr layer and a Ta / ZrN multilayer structural layer; the Zr layer is deposited on the surface of a substrate; the Ta / ZrN multilayer structural layer comprises a Ta layer and a ZrN layer alternately deposited on the surface of the Zr layer; the thickness ratio of the Ta layer to the ZrN layer is 1:0.2-5.
[0008] Directly depositing a single ZrN layer on the surface of a magnesium alloy, the penetration defects in the coating easily lead to insufficient corrosion resistance. The present invention deposits a Zr layer on the surface of the substrate, and alternately deposits a ZrN layer and a Ta layer on the surface of the Zr layer, which can effectively improve the corrosion resistance of the substrate. The reason is that alternately depositing a Ta layer in the ZrN layer can inhibit the growth of columnar crystals in the coating, reduce the penetration defects in the coating, and densify the coating structure. In addition, the magnetron sputtering process is more environmentally friendly than the traditional electroplating process, does not produce environmentally harmful substances, and is conducive to large-scale application.
[0009] In the present invention, the thickness ratio of the Ta layer and the ZrN layer has an influence on the hardness, toughness, internal stress, corrosion resistance, etc. of the coating, and the thickness ratio of the Ta layer and the ZrN layer is 1:0.2 to 5. For example, 1:0.2, 1:1, 1:2, 1:3, 1:4, 1:5, and any thickness within the above-listed numerical ranges are not listed one by one.
[0010] Preferably, the total thickness of the Ta / ZrN multilayer structure layer is 1 μm to 20 μm.
[0011] Preferably, the outermost layer of the Ta / ZrN multilayer structure is a ZrN layer.
[0012] The Zr layer is mainly used as a base layer. The present invention does not specifically limit the thickness ratio of the Ta layer to the Zr layer. The thickness of the Zr layer can be selected according to actual needs. For example, the thickness ratio of the Ta layer to the Zr layer is 1:0.76-2.5.
[0013] A second aspect of the present invention provides a method for preparing a multilayer anti-corrosion coating on the surface of a magnesium alloy, comprising the following steps:
[0014] A Zr layer is deposited on the surface of a substrate by a magnetron sputtering process; then a ZrN layer and a Ta layer are alternately deposited on the surface of the Zr layer to form a Ta / ZrN multilayer structure layer; the thickness ratio of the Ta layer to the ZrN layer is 1:0.2-5.
[0015] The present invention mainly uses magnetron sputtering technology to deposit a Zr layer on the surface of the substrate, and alternately deposits a ZrN layer and a Ta layer on the surface of the Zr layer to form a Ta / ZrN multilayer structure coating. Compared with a single-layer Ta layer, the multilayer anti-corrosion coating of the present invention has higher hardness, wear resistance and corrosion resistance; compared with a single-layer ZrN layer, the multilayer anti-corrosion coating of the present invention is more compact, and the internal stress and brittleness can be greatly reduced.
[0016] Preferably, the total thickness of the Ta / ZrN multilayer structure layer is 1 μm to 20 μm; any value within this range is acceptable, such as 1 μm, 3 μm, 5 μm, 10 μm, 12 μm, 18 μm, 20 μm, and any thickness within the above-listed numerical ranges, which are not listed one by one. Preferably, the number of cycles of alternating deposition of Ta layers and ZrN layers is at least 1, and the outermost layer of the Ta / ZrN multilayer structure layer is a ZrN layer.
[0017] ZrN coating can improve the hardness, wear resistance and corrosion resistance of magnesium alloy substrate. If the coating thickness is too small, its wear resistance and corrosion resistance cannot meet the requirements of harsh working conditions. In order to achieve the required performance effect, it is often necessary to increase the thickness of the ZrN coating, but this often leads to increased internal stress of the coating, and the coating is prone to form a coarse columnar crystal structure, which provides a penetrating channel for corrosive liquids, but affects the performance of the coating. If the thicker ZrN coating is deposited directly on the surface of the metal substrate, it will also have a problem of poor bonding strength due to high internal stress.
[0018] The present invention adopts a method of pre-depositing a Zr layer on the surface of a metal substrate and then alternately depositing a Ta layer and a ZrN layer. Compared with a ZrN coating of the same thickness, the bonding strength is improved, the internal stress of the coating is small, and the degree of organizational refinement is high, thus solving the problem in the prior art that the above-mentioned thickness and performance cannot be taken into account at the same time.
[0019] Preferably, the substrate is a magnesium alloy. The magnesium alloy described in the present invention is an existing magnesium alloy material, for example, the magnesium alloy is AZ31B or other high-hardness magnesium alloys. The magnesium alloy described in the present invention is not limited to AZ31B, but can also be other existing high-hardness magnesium alloys. Of course, the method of the present invention can also be applied to the corrosion protection of other metals and their alloys, for example, the substrate is an aluminum alloy or steel.
[0020] Preferably, the specific preparation method comprises the following steps:
[0021] The Zr target and the Ta target are placed at the sputtering target positions respectively, and the substrate is placed on the sample stage; after evacuation, argon gas is introduced, and a negative bias voltage is applied to the substrate, and the surface of the substrate is cleaned by glow sputtering; argon gas is introduced, the Zr target is magnetron sputtered, and a negative bias voltage is applied to the substrate to form ion bombardment to obtain a Zr layer; argon gas and nitrogen gas are introduced, the Zr target is magnetron sputtered, and a negative bias voltage is applied to the substrate to form ion bombardment to obtain a ZrN layer; argon gas is introduced, the Ta target is magnetron sputtered, and a negative bias voltage is applied to the substrate to form ion bombardment to obtain a Ta layer; the preparation steps of the ZrN layer and the Ta layer are repeated to form a Ta / ZrN multilayer structure layer on the surface of the Zr layer to obtain a multilayer anti-corrosion coating.
[0022] Preferably, the specific method of cleaning the substrate surface by glow sputtering is as follows:
[0023] Evacuate to a vacuum degree of less than 5×10 -3 After 300 Pa, argon gas is introduced, the vacuum degree is controlled at 0.1Pa~0.4Pa, and a bias voltage of -200V~-600V is applied to the substrate to make the gas glow discharge, and the substrate surface is glow sputtered and cleaned by argon ions; the glow sputtering cleaning time is 10min~60min.
[0024] Preferably, the method of depositing the Zr layer is as follows:
[0025] Argon gas is introduced, the vacuum degree is controlled at 0.1Pa to 0.4Pa, and a bias voltage of 0V to -100V is applied to the substrate to form ion bombardment to obtain a Zr layer.
[0026] The method for depositing the Ta layer is as follows:
[0027] Argon gas is introduced, the vacuum degree is controlled at 0.1Pa to 0.4Pa, and a bias voltage of 0V to -100V is applied to the substrate to form ion bombardment to obtain a Ta layer.
[0028] The method for depositing the ZrN layer is as follows:
[0029] Argon and nitrogen are introduced with a flow ratio of 1 to 5:1, the vacuum degree is controlled at 0.1 Pa to 0.4 Pa, and a bias voltage of 0 V to -100 V is applied to the substrate to form ion bombardment to obtain a ZrN layer.
[0030] In the present invention, during the deposition of the ZrN layer, when the nitrogen flow rate is too high, target poisoning is likely to occur, affecting the deposition rate, and the amount of nitrogen exceeding the amount required for the reaction is wasted. Too low nitrogen cannot form enough ZrN, which is equivalent to depositing pure metal Zr. Therefore, the present invention adopts a flow ratio of argon to nitrogen of 1:0.5-10.
[0031] Beneficial effects of the present invention:
[0032] 1. The present invention deposits a Zr layer on the surface of the substrate, and alternately deposits a ZrN layer and a Ta layer on the surface of the Zr layer to form a Ta / ZrN multilayer structure layer, which can reduce the internal stress of the nitride coating, improve the bonding strength between the coating and the magnesium alloy substrate, block the growth of columnar crystals in the coating, densify the coating structure, effectively provide good protection for the substrate, reduce the difficulty of stripping the coating, help improve the wear resistance and corrosion resistance of the magnesium alloy, and solve the problem that defects formed in the existing magnetron sputtering film deposition process will reduce the corrosion resistance and friction resistance of the film.
[0033] 2. The present invention can adjust the hardness, toughness, internal stress and corrosion resistance of the multi-layer anti-corrosion coating by changing the thickness ratio of the Ta layer and the ZrN layer.
[0034] 3. The present invention adopts magnetron sputtering technology, which is greener and more environmentally friendly than the traditional electroplating process, does not produce environmentally harmful substances, and is conducive to large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram of the structure of a multi-layer anti-corrosion coating on a magnesium alloy surface provided in one embodiment of the present invention.
[0036] Figure 2 This is a cross-sectional SEM image of the multi-layer anti-corrosion coating on the surface of the magnesium alloy in Example 1.
[0037] Figure 3 This is a cross-sectional SEM image of a single-layer Ta coating on the surface of the magnesium alloy in Comparative Example 2.
[0038] Figure 4 The potentiodynamic polarization curves of the magnesium alloy and the multi-layer anti-corrosion coating on the surface of the magnesium alloy in Example 1 in a 3.5 wt% NaCl solution are shown in FIG. 1 , wherein Ecorr represents the corrosion potential; and jcorr represents the corrosion current density.
[0039] Figure 5 The SEM images of the multilayer anti-corrosion coating on the surface of the magnesium alloy in Example 1 before and after 24 hours of acidic salt spray. Among them, (a) is the secondary electron morphology before corrosion; (b) is the secondary electron morphology after corrosion; (c) is the backscattered electron morphology before corrosion; (d) is the backscattered electron morphology after corrosion.
[0040] Figure 6 The SEM images of the single-layer Ta coating on the surface of the magnesium alloy in Comparative Example 2 before and after 24h acid salt spray. Among them, (a) is the secondary electron morphology before corrosion; (b) is the secondary electron morphology after corrosion; (c) is the backscattered electron morphology before corrosion; (d) is the backscattered electron morphology after corrosion.
[0041] Figure 7The SEM images of different coatings on the magnesium alloy surface in Examples 1 to 4 and Comparative Examples 1 to 2 after 24 hours of acidic salt spray. Among them, (a) is the backscattered electron morphology of the coating of Comparative Example 2; (b) is the backscattered electron morphology of the coating of Comparative Example 1; (c) is the backscattered electron morphology of the coating of Example 2; (d) is the backscattered electron morphology of the coating of Example 3; (e) is the backscattered electron morphology of the coating of Example 4; (f) is the backscattered electron morphology of the coating of Example 1. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0043] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0044] The technical solution of the present invention is further described below through specific embodiments.
[0045] In the following embodiments, the experimental methods and detection methods are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.
[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] The coating on the surface of magnesium alloy has the problem of easy detachment and poor corrosion resistance, which leads to poor protection effect of the coating on the magnesium alloy substrate. Therefore, improving the bonding strength between the coating and the metal substrate and reducing the penetrating defects in the coating are the basis for improving the corrosion resistance of the coating on the surface of magnesium alloy.
[0048] In order to solve the above problems, an embodiment of the present invention provides a magnesium alloy Ta / ZrN multilayer corrosion-resistant coating, wherein the multilayer corrosion-resistant coating includes a Zr layer and a Ta / ZrN multilayer structure layer; the Zr layer is deposited on the surface of the substrate; the Ta / ZrN multilayer structure layer includes a ZrN layer and a Ta layer alternately deposited on the surface of the Zr layer; the thickness ratio of the Ta layer to the ZrN layer is 1:0.2-5. The total thickness of the Ta / ZrN multilayer structure layer is 1μm-20μm. The Ta / ZrN multilayer structure layer can inhibit the growth of columnar crystals and relieve residual stress in the coating. The corrosion-resistant coating has good bonding with the magnesium alloy substrate.
[0049] A method for preparing a multi-layer anti-corrosion coating on the surface of a magnesium alloy of the present invention comprises the following steps:
[0050] (1) The metal Ta, Zr targets and magnesium alloy are placed on the sputtering target position and sample stage in the vacuum chamber of the magnetron sputtering equipment, respectively.
[0051] (2) The vacuum chamber of the magnetron sputtering equipment is evacuated until the vacuum degree is less than 5×10-3 Pa. Then, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to control the vacuum degree at about 0.2 Pa, and a bias voltage of -200V to -600V is applied to the substrate to bombard and clean the sample surface with argon ions. The glow cleaning time is 10 to 60 minutes.
[0052] (3) Argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to control the vacuum range to 0.1 to 0.4 Pa, and a bias voltage of 0 V to -100 V is applied to the substrate to magnetron sputter the Zr target to obtain a Zr base layer.
[0053] (4) Argon and nitrogen are introduced into the vacuum chamber of the magnetron sputtering equipment, the flow ratio of argon to nitrogen is 1 to 5:1, the vacuum degree is controlled in the range of 0.1 to 0.4 Pa, and a bias voltage of 0 V to -100 V is applied to the substrate to sputter the Zr target to obtain a ZrN layer.
[0054] (5) Argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to control the vacuum degree in the range of 0.1 to 0.4 Pa, and a bias voltage of 0 V to -100 V is applied to the substrate to magnetron sputter a Ta target to obtain a Ta layer.
[0055] (6) Repeat steps (4) and (5) to form a Ta / ZrN multilayer structure layer on the surface of the Zr layer to obtain a multilayer anti-corrosion coating.
[0056] The preparation method of the Ta / ZrN multilayer coating provided by the present invention is to prepare the Ta / ZrN multilayer coating by magnetron sputtering, which can reduce the internal stress of the nitride coating, improve the bonding strength between the coating and the magnesium alloy substrate, inhibit the growth of columnar crystals in the coating, and densify the coating structure, which can effectively provide good protection for the substrate, reduce the difficulty of stripping the coating, and help improve the wear resistance and corrosion resistance of the magnesium alloy. The preparation method of the Ta / ZrN multilayer corrosion-resistant coating provided by the present invention can adjust the hardness, toughness, internal stress and corrosion resistance of the coating by changing the thickness ratio of the Ta layer and the ZrN layer. The preparation method of the ablation-resistant Ta / ZrN multilayer coating provided by the present invention is more environmentally friendly than traditional electroplating chromium and does not produce environmentally harmful substances.
[0057] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments.
[0058] Example 1
[0059] A method for preparing a multi-layer anti-corrosion coating on a magnesium alloy surface, such as Figure 1 As shown, the following steps are included:
[0060] 1) Using AZ31B as a substrate, the AZ31B substrate is ground, polished, cleaned, and dried, and then fixed on a rotatable workpiece holder in a vacuum chamber.
[0061] 2) After the vacuum chamber of the magnetron sputtering equipment is evacuated to ≤4×10-3Pa, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2Pa, and a -500V bias is applied to the substrate, and the substrate surface is cleaned by glow plasma sputtering for 30 minutes.
[0062] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Zr layer with a thickness of 500 nm.
[0063] 4) Argon and nitrogen were introduced into the vacuum chamber of the magnetron sputtering equipment, with an Ar:N2 flow ratio of 2:1 and a gas pressure of 0.2 Pa. The Zr target was sputtered at a power of 2000 W, and a -60 V bias was applied to the substrate to deposit a ZrN layer with a thickness of 500 nm.
[0064] 5) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Ta target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Ta layer with a thickness of 500 nm.
[0065] 6) Repeating the above steps 4) and 5) alternately, wherein the outermost layer is a ZrN layer, to obtain a TaZrN multilayer corrosion-resistant coating with a total thickness of 3 μm. The thickness ratio of the Ta layer to the ZrN layer in the Ta / ZrN multilayer corrosion-resistant coating is 1:1.
[0066] Example 2
[0067] A method for preparing a multi-layer anti-corrosion coating on the surface of a magnesium alloy comprises the following steps:
[0068] 1) Using AZ31B as a substrate, the AZ31B substrate is ground, polished, cleaned, and dried, and then fixed on a rotatable workpiece holder in a vacuum chamber.
[0069] 2) After the vacuum chamber of the magnetron sputtering equipment is evacuated to ≤4×10-3Pa, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2Pa, and a -500V bias is applied to the substrate, and the substrate surface is cleaned by glow plasma sputtering for 30 minutes.
[0070] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Zr layer with a thickness of 500 nm.
[0071] 4) Argon and nitrogen were introduced into the vacuum chamber of the magnetron sputtering equipment, with an Ar:N2 flow ratio of 2:1 and a gas pressure of 0.2 Pa. The Zr target was sputtered at a power of 2000 W, and a -60 V bias was applied to the substrate to deposit a ZrN layer with a thickness of 450 nm.
[0072] 5) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Ta target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Ta layer with a thickness of 650 nm.
[0073] 6) Repeating the above steps 4) and 5) alternately, wherein the outermost layer is a ZrN layer, to obtain a Ta / ZrN multilayer corrosion-resistant coating with a total thickness of 3 μm. The thickness ratio of the Ta layer to the ZrN layer in the Ta / ZrN multilayer corrosion-resistant coating is 13:8.
[0074] Example 3
[0075] A method for preparing a multi-layer anti-corrosion coating on the surface of a magnesium alloy comprises the following steps:
[0076] 1) Using AZ31B as a substrate, the AZ31B substrate is ground, polished, cleaned, and dried, and then fixed on a rotatable workpiece holder in a vacuum chamber.
[0077] 2) After the vacuum chamber of the magnetron sputtering equipment is evacuated to ≤4×10-3Pa, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2Pa, and a -500V bias is applied to the substrate, and the substrate surface is cleaned by glow plasma sputtering for 30 minutes.
[0078] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Zr layer with a thickness of 500 nm.
[0079] 4) Argon and nitrogen were introduced into the vacuum chamber of the magnetron sputtering equipment, with an Ar:N2 flow ratio of 2:1 and a gas pressure of 0.2 Pa. The Zr target was sputtered at a power of 2000 W, and a bias of -60 V was applied to the substrate to deposit a ZrN layer with a thickness of 700 nm.
[0080] 5) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Ta target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Ta layer with a thickness of 200 nm.
[0081] 6) Repeating the above steps 4) and 5) alternately, wherein the outermost layer is a ZrN layer, to obtain a Ta / ZrN multilayer corrosion-resistant coating with a total thickness of 3 μm. The thickness ratio of the Ta layer to the ZrN layer in the Ta / ZrN multilayer corrosion-resistant coating is 2:7.
[0082] Example 4
[0083] A method for preparing a multi-layer anti-corrosion coating on the surface of a magnesium alloy comprises the following steps:
[0084] 1) Pure magnesium is used as a substrate, and the magnesium substrate is ground, polished, cleaned, and dried, and then fixed on a rotatable workpiece holder in a vacuum chamber.
[0085] 2) After the vacuum chamber of the magnetron sputtering equipment is evacuated to ≤4×10-3Pa, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2Pa, and a -500V bias is applied to the substrate, and the substrate surface is cleaned by glow plasma sputtering for 30 minutes.
[0086] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Zr layer with a thickness of 500 nm.
[0087] 4) Argon and nitrogen were introduced into the vacuum chamber of the magnetron sputtering equipment, with an Ar:N2 flow ratio of 5:1 and a gas pressure of 0.2 Pa. The Zr target was sputtered at a power of 2000 W, and a -60 V bias was applied to the substrate to deposit a ZrN layer with a thickness of 500 nm.
[0088] 5) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Ta target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Ta layer with a thickness of 500 nm.
[0089] 6) Repeating the above steps 4) and 5) alternately, wherein the outermost layer is a ZrN layer, to obtain a Ta / ZrN multilayer corrosion-resistant coating with a total thickness of 3 μm. The thickness ratio of the Ta and ZrN layers in the Ta / ZrN multilayer corrosion-resistant coating is 1:1.
[0090] Comparative Example 1
[0091] The method for preparing a single-layer ZrN coating on the surface of a magnesium alloy, compared with Example 1, is to deposit a ZrN layer of the same thickness only on the surface of the substrate. The specific preparation method comprises the following steps:
[0092] 1) Using AZ31B as a substrate, the AZ31B substrate is ground, polished, cleaned, and dried, and then fixed on a rotatable workpiece holder in a vacuum chamber.
[0093] 2) After the vacuum chamber of the magnetron sputtering equipment is evacuated to ≤4×10-3Pa, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2Pa, and a -500V bias is applied to the substrate, and the substrate surface is cleaned by glow plasma sputtering for 30 minutes.
[0094] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Zr layer with a thickness of 500 nm.
[0095] 4) Introduce argon and nitrogen into the vacuum chamber of the magnetron sputtering equipment, Ar:N 2 The flow ratio was 2:1, the gas pressure was 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a -60 V bias was applied to the substrate to deposit a single-layer ZrN coating with a total thickness of 3 μm.
[0096] Comparative Example 2
[0097] The method for preparing a single-layer Ta coating on the surface of a magnesium alloy, compared with Example 1, is to deposit a Ta layer of the same thickness only on the surface of the substrate. The specific preparation method comprises the following steps:
[0098] 1) Using AZ31B as a substrate, the AZ31B substrate is ground, polished, cleaned, and dried, and then fixed on a rotatable workpiece holder in a vacuum chamber.
[0099] 2) After the vacuum chamber of the magnetron sputtering equipment is evacuated to ≤4×10-3Pa, argon gas is introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2Pa, and a -500V bias is applied to the substrate, and the substrate surface is cleaned by glow sputtering for 30 minutes.
[0100] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Zr target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a Zr layer with a thickness of 500 nm.
[0101] 4) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, the Ta target was sputtered at a power of 2000 W, and a bias voltage of -60 V was applied to the substrate to deposit a single-layer Ta coating with a total thickness of 3 μm.
[0102] Table 1 Comparison of conditions
[0103]
[0104] Test 1: SEM analysis.
[0105] Figure 1 A schematic diagram of the structure of a multi-layer anti-corrosion coating on a magnesium alloy surface provided in one embodiment of the present invention. Figure 2 The cross-sectional SEM image of the multi-layer anti-corrosion coating on the surface of the magnesium alloy in Example 1. Figure 2 It can be seen that the light-colored layer corresponds to Ta, and the dark-colored layer corresponds to ZrN. It can be seen that the ZrN layer and the Ta layer are grown alternately in the coating.
[0106] Figure 3 This is a cross-sectional SEM image of a single-layer Ta coating on the surface of the magnesium alloy in Comparative Example 2. Figure 3 It can be seen that there are a large number of columnar crystals in the coating.
[0107] From the above analysis, it can be seen that Example 1 of the present invention uses magnetron sputtering technology to prepare a multilayer anti-corrosion coating on the surface of a magnesium alloy with excellent corrosion resistance. Compared with the single-layer Ta coating of Comparative Example 2, the Ta / ZrN multilayer corrosion-resistant coating formed alternately in Example 1 of the present invention can avoid the columnar crystal structure formed when the single-layer coating is prepared by magnetron sputtering, thereby avoiding the formation of corrosive medium channels formed by coarse columnar crystal boundaries. Compared with the single-layer ZrN coating, the Ta / ZrN multilayer corrosion-resistant coating formed in Example 1 of the present invention has a denser coating structure, thereby improving the hardness of the coating and significantly reducing the internal stress and brittleness.
[0108] This proves that the method of Example 1 of the present invention can improve the hardness, wear resistance and corrosion resistance of the Ta / ZrN multilayer corrosion-resistant coating.
[0109] Test 2: Corrosion resistance analysis.
[0110] Figure 4 The potentiodynamic polarization curves of the magnesium alloy and the multi-layer anti-corrosion coating on the surface of the magnesium alloy in Example 1 in a 3.5 wt% NaCl solution are shown in FIG. 1 , wherein Ecorr represents the corrosion potential; and jcorr represents the corrosion current density.
[0111] from Figure 4 It can be seen that the corrosion current density of the multilayer anti-corrosion coating on the surface of the magnesium alloy in Example 1 is significantly reduced, and the corrosion potential is significantly increased. This shows that compared with the magnesium alloy, the corrosion resistance of the multilayer anti-corrosion coating on the surface of the magnesium alloy in Example 1 is indeed improved.
[0112] Figure 5 The SEM images of the multilayer anti-corrosion coating on the surface of the magnesium alloy in Example 1 before and after 24 hours of acidic salt spray. Among them, (a) is the secondary electron morphology before corrosion; (b) is the secondary electron morphology after corrosion; (c) is the backscattered electron morphology before corrosion; (d) is the backscattered electron morphology after corrosion.
[0113] Depend on Figure 5 It can be seen that after the multi-layer anti-corrosion coating on the surface of the magnesium alloy in Example 1 was corroded by acidic salt spray for 24 hours, the magnesium alloy substrate was not exposed.
[0114] Figure 6 The SEM images of the single-layer Ta coating on the surface of the magnesium alloy in Comparative Example 2 before and after 24h acid salt spray. Among them, (a) is the secondary electron morphology before corrosion; (b) is the secondary electron morphology after corrosion; (c) is the backscattered electron morphology before corrosion; (d) is the backscattered electron morphology after corrosion.
[0115] Depend on Figure 6 It can be seen that after 24 hours of acid salt spray corrosion, the single-layer Ta coating on the surface of the magnesium alloy in Comparative Example 2 has exposed the magnesium alloy substrate.
[0116] Through the above data analysis, it can be seen that the multi-layer anti-corrosion coating on the surface of the magnesium alloy in Example 1 of the present invention can effectively suppress defects in the coating, prevent the generation of corrosion voids and cracks, protect the base magnesium alloy from corrosion during acidic salt spray, and improve the overall corrosion resistance of the magnesium alloy.
[0117] Test 3: Effect of different thickness ratios of Ta layer and ZrN layer on coating performance.
[0118] The hardness and corrosion resistance of the Ta / ZrN multilayer corrosion-resistant coatings prepared in Examples 1 to 4, the single-layer ZrN coating prepared in Comparative Example 1, and the single-layer Ta coating prepared in Comparative Example 2 were analyzed. The results are shown in Tables 2 and Figure 7 shown.
[0119] Table 2 Effect of different thickness ratios of Ta layer and ZrN layer on coating performance
[0120]
[0121]
[0122] The analysis results in Table 2 show that with the increase of the thickness of the ZrN layer, the hardness of the prepared coating gradually increases. And the corrosion resistance also varies with the change of the thickness ratio of the ZrN layer to the Ta layer.
[0123] Figure 7 The SEM images of different coatings on the magnesium alloy surface in Examples 1 to 4 and Comparative Examples 1 to 2 after 24 hours of acidic salt spray. Among them, (a) is the backscattered electron morphology of the coating of Comparative Example 2; (b) is the backscattered electron morphology of the coating of Comparative Example 1; (c) is the backscattered electron morphology of the coating of Example 2; (d) is the backscattered electron morphology of the coating of Example 3; (e) is the backscattered electron morphology of the coating of Example 4; (f) is the backscattered electron morphology of the coating of Example 1.
[0124] The backscattered electron morphology of the coating surface after 24 hours of acid salt spray can be seen. Figure 7 As shown in Figure (a), the single-layer Ta coating was almost completely corroded to the substrate within 24 hours, showing poor corrosion resistance. Figure 7 (b) shows that although a single ZrN layer can improve the hardness of the coating, a large number of columnar crystals allow the corrosive medium to corrode the substrate, resulting in poor corrosion resistance.
[0125] Figure 7 In Figures (c) to (f), there are only a few pitting holes on the surface of the Ta / ZrN multilayer coating, and the corrosion resistance is improved. The number of pitting holes changes with the change of the thickness ratio of the Ta layer and the ZrN layer.
[0126] The above analysis shows that, compared with Comparative Examples 1 and 2, the method of the embodiment of the present invention can effectively adjust the hardness, toughness, internal stress and corrosion resistance of the coating by changing the thickness ratio of the Ta layer and the ZrN layer.
[0127] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-layer anti-corrosion coating on the surface of a magnesium alloy, characterized in that: The multi-layer anti-corrosion coating comprises a Zr layer and a Ta / ZrN multi-layer structure layer; The Zr layer is deposited on the surface of the substrate; The Ta / ZrN multilayer structure layer comprises ZrN layers and Ta layers alternately deposited on the surface of the Zr layer; the thickness ratio of the Ta layer to the ZrN layer is 1:0.2-5.
2. The multi-layer anti-corrosion coating on the surface of magnesium alloy according to claim 1, characterized in that: The total thickness of the Ta / ZrN multilayer structure layer is 1 μm to 20 μm.
3. The multi-layer anti-corrosion coating on the surface of magnesium alloy according to claim 1, characterized in that: The outermost layer of the Ta / ZrN multilayer structure is a ZrN layer.
4. A method for preparing a multilayer anti-corrosion coating on a magnesium alloy surface, characterized in that: The following steps are involved: A Zr layer is deposited on the substrate surface by a magnetron sputtering process; Then, ZrN layers and Ta layers are alternately deposited on the surface of the Zr layer to form a Ta / ZrN multilayer structure layer; The thickness ratio of the Ta layer to the ZrN layer is 1:0.2-5.
5. The method for preparing a multi-layer anti-corrosion coating on a magnesium alloy surface according to claim 4, characterized in that: The total thickness of the Ta / ZrN multilayer structure layer is 1 μm to 20 μm; the number of cycles of alternately depositing Ta layers and ZrN layers is at least 1, and the outermost layer of the Ta / ZrN multilayer structure layer is a ZrN layer.
6. The method for preparing a multi-layer anti-corrosion coating on a magnesium alloy surface according to claim 4, characterized in that: The substrate is a magnesium alloy.
7. The method for preparing a multi-layer anti-corrosion coating on a magnesium alloy surface according to claim 4, characterized in that: The specific preparation method comprises the following steps: The Zr target and the Ta target are placed at the sputtering target positions respectively, and the substrate is placed on the sample stage; after vacuuming, argon gas is introduced, and a negative bias voltage is applied to the substrate, and the substrate surface is cleaned by glow sputtering; Argon gas is introduced to magnetron sputter a Zr target, and a negative bias voltage is applied to the substrate to form ion bombardment to obtain a Zr layer; Argon and nitrogen are introduced to magnetron sputter a Zr target, and a negative bias is applied to the substrate to form ion bombardment to obtain a ZrN layer; Argon gas is introduced to magnetron sputter a Ta target, and a negative bias voltage is applied to the substrate to form ion bombardment to obtain a Ta layer; The steps of preparing the ZrN layer and the Ta layer are repeated to form a Ta / ZrN multilayer structure layer on the surface of the Zr layer to obtain a multilayer anti-corrosion coating.
8. The method for preparing a multi-layer anti-corrosion coating on a magnesium alloy surface according to claim 7, characterized in that: The specific method of cleaning the substrate surface by glow sputtering is as follows: Evacuate to a vacuum degree of less than 5×10 -3 After 300 Pa, argon gas is introduced, the vacuum degree is controlled at 0.1Pa~0.4Pa, and a bias voltage of -200V~-600V is applied to the substrate to make the gas glow discharge, and the substrate surface is glow sputtered and cleaned by argon ions; the glow sputtering cleaning time is 10min~60min.
9. The method for preparing a multi-layer anti-corrosion coating on a magnesium alloy surface according to claim 7, characterized in that: The method for depositing the Zr layer is as follows: Argon gas is introduced, the vacuum degree is controlled at 0.1Pa to 0.4Pa, and a bias voltage of 0V to -100V is applied to the substrate to form ion bombardment to obtain a Zr layer; The method for depositing the Ta layer is as follows: Argon gas is introduced, the vacuum degree is controlled at 0.1Pa to 0.4Pa, and a bias voltage of 0V to -100V is applied to the substrate to form ion bombardment to obtain a Ta layer; The method for depositing the ZrN layer is as follows: Argon and nitrogen are introduced with a flow ratio of 1 to 5:1, the vacuum degree is controlled at 0.1 Pa to 0.4 Pa, and a bias voltage of 0 V to -100 V is applied to the substrate to form ion bombardment to obtain a ZrN layer.
Citation Information
Patent Citations
Method for preparing tantalum film on surface of magnesium alloy through magnetron sputtering deposition
CN102703874A
Method for preparing conductive anti-corrosion coating on magnesium alloy surface
CN103774092A
Vapor deposition method used for anticorrosion pretreatment of permanent magnet
CN105420669A
Preparation method of erosion-resistant anti-corrosion self-cleaning coating of compressor blade
CN111005002A
Biomedical metal surface multi-layer coating and preparation method thereof
CN111041415A
Cited By
Corrosion-resistant coating for wading fastener and preparation method of corrosion-resistant coating
CN121183279A